2022
DOI: 10.1002/macp.202100421
|View full text |Cite
|
Sign up to set email alerts
|

Thieno[3,4‐c]pyrrole‐4,6‐dione‐Based Conjugated Polymers for Nonfullerene Organic Solar Cells

Abstract: Donor-acceptor (D-A) conjugated polymers have gotten significant attention in the past decades. Wide application area, ease of production, and cost-effectiveness have made the D-A conjugated polymers a pivotal class of organic electronics. Organic solar cells (OSCs) became one of the most critical application areas of conjugated polymers among many. Up to the last decade, intensive research has been conducted on fullerene-based OSCs. Drawbacks of fullerene derivatives like high cost, production obstacles, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…[41][42][43] Historically speaking, the creation of new imide-functionalized unit played a crucial role in the evolution of imidefunctionalized polymers. Till now, many imide building units have been created or developed, including naphthalene diimide (NDI), [44] perylene diimide (PDI), [26,45] thieno [3,4-c]pyrrole-4,6-dione (TPD), [39,46,47] phthalimide (PHI), [48,49] pyrrolo [3,4-f ] benzotriazole-5,7(6H )-dione (TzBI), [50,51] dithienophthalimide (DPI), [35,52] naphthalenothiophene imide (NTI), [22] bithiophene imide (BTI) units, [53,54] naphthodithiophene imide (NDTI), [55] thieno[3,4-f]isoindole-5,7-dione unit (TID), [25,56] 5,9-di(thiophen-2-yl)-6H -pyrrolo[3,4g ]quinoxaline-6,8(7H )-dione (PQD), [57,58] N-alkyl-4,7-di(thien-2-yl)-2,1,3-benzothiadiazole-5,6-dicarboxylic imide (DI), [59,60] pyromellitic diimide (PMDI), [61] tetraazabenzodifluoranthene diimide (BFI). [62] The chemical structure of various imide-functionalized building units are illustrated in Figure 1.…”
Section: Imide-functionalized Building Unitsmentioning
confidence: 99%
See 3 more Smart Citations
“…[41][42][43] Historically speaking, the creation of new imide-functionalized unit played a crucial role in the evolution of imidefunctionalized polymers. Till now, many imide building units have been created or developed, including naphthalene diimide (NDI), [44] perylene diimide (PDI), [26,45] thieno [3,4-c]pyrrole-4,6-dione (TPD), [39,46,47] phthalimide (PHI), [48,49] pyrrolo [3,4-f ] benzotriazole-5,7(6H )-dione (TzBI), [50,51] dithienophthalimide (DPI), [35,52] naphthalenothiophene imide (NTI), [22] bithiophene imide (BTI) units, [53,54] naphthodithiophene imide (NDTI), [55] thieno[3,4-f]isoindole-5,7-dione unit (TID), [25,56] 5,9-di(thiophen-2-yl)-6H -pyrrolo[3,4g ]quinoxaline-6,8(7H )-dione (PQD), [57,58] N-alkyl-4,7-di(thien-2-yl)-2,1,3-benzothiadiazole-5,6-dicarboxylic imide (DI), [59,60] pyromellitic diimide (PMDI), [61] tetraazabenzodifluoranthene diimide (BFI). [62] The chemical structure of various imide-functionalized building units are illustrated in Figure 1.…”
Section: Imide-functionalized Building Unitsmentioning
confidence: 99%
“…[46] In ad-dition, Various side groups can be introduced into the N-site of TPD to tune solubility of the resulting polymer and morphology of blend films. [39,46] To date, four synthetic routes have been reported for the preparation of TPD (Scheme 2) . Bjørnholm et al [74] reported the synthesis of TPD from starting materials of 3, 4-dibromothiophene, which was converted to 3, 4-dicyanothiophene by Rosenmund-von Braun reaction with cuprous cyanide (Synthetic route 1).…”
Section: Imide-functionalized Building Unitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering π-conjugated systems, the most successful frameworks generally possess electron "push -pull" structures, achieved via the combination of electron-poor acceptor units with electron-rich donor moieties [45]. Among the electron-accepting-type frameworks, the thieno [3,4-c]pyrrole-4,6-dione (TPD) scaffold, one of the promising electron-accepting units, has several advantages, mainly providing facile synthesis, great coplanarity, a robust π-π stacking feature, and strong electron transporting, owing to the ease of switching to its quinoid form [46]. In addition to these, this unique symmetric scaffold can be modified not only with numerous functional groups from the reactive sides of the α-positions of the thiophene heterocyclic ring, but also further with N-alkylation to gain new functionalities by preserving its remarkable optoelectronic properties [47].…”
Section: Introductionmentioning
confidence: 99%